Holes [videorecording (DVD)] - Davis, Andrew, 1946-; Weaver, Sigourney, 1949-; Voight, Jon, 1938-; Arquette, Patricia, 1968- (Disney DVD : Distributed by Buena Vista Home Entertainment, 2003)
Young Stanley Yelnats finds himself at Camp Green Lake, where digging a hole a day keeps the warden at bay and "builds character". An ancient family curse still dogs Stanley and he's thrown headlong into the adventure of his life. Stanley and his campmates will have to forge fast friendships to unearth the mystery of what's really going on in the desert.